On the Use of Nudges to Affect Spillovers in Environmental Behaviors - Fanghella, Valeria; d’Adda, Giovanna; Tavoni, Massimo (Frontiers in Psychology, 2019)
Environmental self-identity is considered a promising lever to generate positive spillovers across pro-environmental behaviors: existing evidence shows that it is positively correlated with pro-environmental choices and that it can be easily manipulated, by reminding individuals of their past pro-environmental actions. However, it remains unclear whether it can be successfully used for environmental policy making. In two online, incentive-compatible experiments, we manipulate participants’ environmental self-identity and test whether this leads to increased donations to an environmental charity. Additionally, we investigate the interaction between self-identity priming and two commonly used behavioral policy tools: social information (Study 1, N=400) and goal commitment (Study 2, N= 495). Our results suggest caution in leveraging environmental self-identity to promote pro-environmental behaviors, provide indications on how to target policies based on self-identity primes, and offer novel evidence on the interaction between different behavioral policy tools.